Secondary battery and manufacturing method thereof

Semi-solid electrodes with controlled particle size distribution and a simplified manufacturing process address the issues of electrical resistance and structural changes in conventional batteries, enhancing rate and cycle characteristics while reducing costs.

JP2025014074AInactive Publication Date: 2025-01-29MURATA MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021165049
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-10-06
Publication Date
2025-01-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional secondary batteries face issues with increased electrical resistance due to the presence of binders, leading to decreased rate characteristics, and have complex manufacturing processes that increase costs and result in changes to the electrode's internal structure over time, affecting cycle characteristics.

Method used

The use of semi-solid electrodes with controlled particle size distribution (D10 > R) and the absence of binders, combined with a simplified manufacturing process, including grain diameter adjustment, mixing, laminating, and enclosing steps, to stabilize the electrode structure and enhance rate and cycle characteristics.

Benefits of technology

The solution effectively suppresses changes in the electrode's internal structure over time, reduces manufacturing complexity and costs, and improves rate and cycle characteristics by minimizing electrical resistance without binders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014074000001_ABST
    Figure 2025014074000001_ABST
Patent Text Reader

Abstract

To provide a secondary battery in which the internal structure of an electrode is further prevented from changing over time and which has sufficiently excellent rate characteristics and cycle characteristics.SOLUTION: A secondary battery includes a semi-solid electrode having an electrode active material and an electrolyte, and the particle size distribution of the electrode active material satisfies the relation: D10 (μm)>r (μm), r is the diameter of a sphere inscribed in a gap between four closely packed spheres of D90 (μm), and is represented by the following formula (1).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery, in particular a secondary battery including a semi-solid electrode, and a method for producing the same. [Background technology]

[0002] Conventionally, secondary batteries have been used as power sources for various electronic devices. A secondary battery generally has a structure in which a laminate in which a positive electrode having a positive electrode layer and a negative electrode having a negative electrode layer are alternately laminated with a separator interposed therebetween, and an electrolyte is contained within an exterior body. In addition, as electrodes such as a positive electrode and a negative electrode, a binder-bonded electrode in which an electrode active material, a conductive assistant, and the like are bound by a binder on a current collector is used.

[0003] On the other hand, secondary batteries using semi-solid electrodes having fluidity instead of binder-bonded electrodes are known for the purposes of simplifying and reducing manufacturing costs, reducing inactive components in electrodes and secondary batteries, and improving energy density, charge capacity, and overall performance (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2016-500465 Summary of the Invention [Problem to be solved by the invention]

[0005] The inventors of the present invention have found that the following new problems may arise in conventional secondary batteries.

[0006] (1) In the binder-bonded electrode, the binder is present in a relatively large amount, which hinders the movement of electrons and ions and increases the electrical resistance, resulting in a decrease in rate characteristics.

[0007] (2) A method for producing a secondary battery including a binder-bonded electrode includes, as electrode production steps, a preparation step of preparing an electrode layer-forming coating liquid; a coating step of coating a current collector with the electrode layer-forming coating liquid; a drying step of drying the coated electrode layer; a pressing step of compacting the electrode precursor; a slitting step of cutting the electrode precursor to a desired width; and a cutting step of cutting the electrode precursor to a desired size to form an electrode; and, as assembly steps, a welding step of connecting tabs to the electrodes; a lamination step of laminating the electrodes so that the positive electrodes and negative electrodes are arranged alternately with a separator arranged between them to produce a laminate; a liquid injection step of sandwiching the produced laminate within an exterior body and injecting an electrolyte into the exterior body; a vacuum impregnation step of impregnating the electrodes with the electrolyte while maintaining a vacuum inside the exterior body; an encapsulation step of enclosing the laminate in the exterior body; a charge-discharge step of forming a solid electrolyte interface coating on the surface of the negative electrode active material by an initial charging treatment to form a secondary battery precursor; and an aging step of aging the secondary battery precursor. Such a complicated and lengthy manufacturing process increases the capital investment and manufacturing process costs, raising the manufacturing cost of the secondary battery.

[0008] (3) Semi-solid electrodes can be made much thicker than conventional electrodes, so the ratio of active material to inactive material (i.e., current collectors and separators) can be higher in batteries using semi-solid electrodes than in secondary batteries using conventional electrodes. This significantly increases the charge capacity and overall energy density of secondary batteries containing semi-solid electrodes. However, in secondary batteries containing semi-solid electrodes, the active material and conductive additives are not fixed by a binder, so the active material particles settle, causing the internal structure of the electrode to change over time, and battery performance changes. Specifically, the rate characteristics and cycle characteristics are degraded.

[0009] An object of the present invention is to provide a secondary battery in which the internal structure of an electrode is prevented from changing over time and which is sufficiently excellent in rate characteristics and cycle characteristics, and a method for producing the same.

[0010] Another object of the present invention is to provide a secondary battery that suppresses changes in the internal structure of the electrode over time, has sufficiently excellent rate characteristics and cycle characteristics, and can be manufactured with fewer manufacturing steps, and a manufacturing method thereof. [Means for solving the problem]

[0011] The present invention relates to A semi-solid electrode having an electrode active material and an electrolyte, The particle size distribution of the electrode active material has the following relationship: D10 (μm)>r (μm) (where r is the diameter of a sphere inscribed in a tetrahedral gap formed by four spheres of close packing D90 (μm)), and is expressed by the following formula (1):

number

[0012] The present invention also provides The present invention relates to a method for producing the above-mentioned secondary battery, the method comprising the steps of: a particle size adjusting step of adjusting the particle size of the electrode active material; a preparation step of mixing the particle size-adjusted electrode active material and an electrolyte solution to prepare a slurry for an electrode layer; A coating process of coating a current collector with a slurry for an electrode layer to form an electrode; a lamination step of laminating the electrodes to form a laminate such that a separator is disposed between the electrodes; An encapsulation step of encapsulating the laminate in an exterior case. Effect of the Invention

[0013] In the secondary battery of the present invention, it is possible to suppress changes over time in the internal structure of the electrode due to factors such as settling of active material particles, and the secondary battery has sufficiently excellent rate characteristics and cycle characteristics. In the secondary battery of the present invention, the secondary battery manufacturing process can be significantly simplified, so that the capital investment cost and manufacturing process cost can be significantly reduced. In addition, the secondary battery of the present invention does not contain a binder, so that low resistance can be realized, and therefore the rate characteristics are sufficiently excellent. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic diagram illustrating the diameter r of a sphere inscribed in a tetrahedral gap formed by four closely packed D90 spheres. [Diagram 2] FIG. 2 is a schematic diagram for explaining the mechanism by which the internal structure of the electrode in the secondary battery according to one embodiment of the present invention is prevented from changing over time. [Diagram 3] FIG. 3 is a schematic diagram for explaining how the internal structure of an electrode in a conventional secondary battery changes over time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention provides a secondary battery. In this specification, the term "secondary battery" refers to a battery that can be repeatedly charged and discharged. The term "secondary battery" is not limited to its name, and may also include electrochemical devices such as "electricity storage devices". In this specification, "planar view" refers to a state (top view or bottom view) when an object is viewed from above or below (particularly from above) along the thickness direction (for example, the stacking direction of electrodes and separators). In this specification, "cross-sectional view" refers to a cross-sectional state (cross-sectional view) when viewed from a direction perpendicular to the thickness direction. It should be noted that the various elements shown in the drawings are merely shown diagrammatically for understanding the present invention, and that the dimensional ratio and appearance may differ from the actual objects. The "up-down direction", "left-right direction", and "front-back direction" used directly or indirectly in this specification correspond to the up-down direction, left-right direction, and front-back direction in the drawings, respectively. Unless otherwise specified, the same symbols or symbols indicate the same members or the same meanings. In a preferred embodiment, the vertical downward direction (i.e., the direction in which gravity acts) can be considered to correspond to the "downward direction", and the opposite direction can be considered to correspond to the "upward direction".

[0016] The secondary battery of the present invention will be described in detail below. The secondary battery of the present invention has a semi-solid electrode. The semi-solid electrode has a semi-solid electrode layer and a current collector. The semi-solid electrode layer is usually a layer containing an electrode active material, a conductive assistant, and an electrolyte, and has fluidity. In the present invention, the electrode active material may be simply referred to as an active material or active material particles. The semi-solid electrode is also referred to as a clay electrode because it has a semi-solid electrode layer. In the present invention, each member constituting the secondary battery is disposed on each of the positive electrode and the negative electrode, unless otherwise specified. For example, the semi-solid electrode includes a semi-solid positive electrode and a semi-solid negative electrode. In this case, the semi-solid positive electrode includes a positive electrode current collector and a semi-solid positive electrode layer disposed on at least one surface of the positive electrode current collector. The semi-solid negative electrode includes a negative electrode current collector and a semi-solid negative electrode layer disposed on at least one surface of the negative electrode current collector. In addition, for example, the electrode active material (or active material) includes a positive electrode active material and a negative electrode active material. For example, the conductive assistant includes a positive electrode conductive assistant and a negative electrode conductive assistant. For example, the electrolyte includes a positive electrode electrolyte and a negative electrode electrolyte. The positive electrode electrolyte and the negative electrode electrolyte may usually be electrolytes of the same composition. The conductive assistant does not necessarily have to be included in the semi-solid positive electrode and the semi-solid negative electrode. For example, both the positive electrode and the negative electrode may each include a conductive assistant, or both may not. For example, the positive electrode may include a conductive assistant and the negative electrode may not include a conductive assistant. For example, the positive electrode may not include a conductive assistant and the negative electrode may include a conductive assistant. The conductive assistant is usually included in at least the positive electrode.

[0017] In the present invention, both electrodes (i.e., positive and negative electrodes) are usually semi-solid electrodes. Thus, the positive and negative electrodes correspond to a semi-solid positive electrode and a semi-solid negative electrode, respectively. In other words, the secondary battery of the present invention includes a semi-solid positive electrode and a semi-solid negative electrode, and at least one of the semi-solid positive electrode and the semi-solid negative electrode corresponds to a semi-solid electrode. The term "semi-solid electrode" means that the electrode layer (particularly the material) is a mixture of a solid phase and a liquid phase, and the mixture may have the form of, for example, a slurry, a colloidal suspension, an emulsion, a gel, or a micelle or particle suspension. Thus, the electrode layer of the semi-solid electrode (i.e., the semi-solid electrode layer) is specifically composed of a slurry containing an electrode active material (usually solid-phase particles, sometimes simply referred to as active material particles) and an electrolyte (usually liquid phase), and may further contain additives such as a conductive assistant (usually solid-phase particles). Unlike conventional binder-bound electrode layers, such a semi-solid electrode layer does not contain a binder for binding and / or fixing the electrode active materials to each other. In the present invention, since the electrode (particularly the electrode layer) does not contain such a binder, it is possible to avoid an increase in electrical resistance caused by the binder, and it is possible to achieve a further increase in the capacity of the secondary battery. In the present invention, the semi-solid electrode (particularly the semi-solid electrode layer) does not strictly have to contain no binder. The present invention does not prevent the inclusion of a trace amount of binder as an impurity unintentionally mixed into the electrode layer during the manufacturing process. From this perspective, the content of the binder contained in the semi-solid electrode (particularly the semi-solid electrode layer) may be 0.1 mass % or less, particularly 0.01 mass % or less, based on the total amount of the semi-solid electrode layer. The content of the binder may be within the above range in each of the semi-solid positive electrode layer or the semi-solid negative electrode layer (particularly the semi-solid positive electrode layer).

[0018] In the secondary battery of the present invention, the particle size distribution of the electrode active material contained in the semi-solid electrode satisfies the relation: D10 (μm)>r (μm), where r is the diameter of a sphere inscribed in a gap between four closely packed tetrahedrons of D90 (μm), and satisfies the following formula (1):

number

[0019] Specifically, the above relational expression relates to the particle diameter D10 (μm) of the active material contained in the semi-solid electrode (particularly the semi-solid electrode layer) and the r (μm) of the active material contained in the semi-solid electrode (particularly the semi-solid electrode layer). More specifically, the particle diameter D10 (μm) of the active material is greater than the diameter r (μm) of the sphere inscribed in the gap of a tetrahedron formed by four spheres of D90 (μm) of the active material. As described in detail later, the above r is the diameter of the sphere inscribed in the gap of a tetrahedron formed by four spheres of D90 (μm) that are closely packed, and r may also be simply referred to as the inscribed sphere diameter.

[0020] The above-mentioned relationship may be achieved by the electrode active material in at least one of the semi-solid electrodes, the semi-solid positive electrode or the semi-solid negative electrode. In detail, for example, the above-mentioned relationship may be achieved by the electrode active material in both the semi-solid positive electrode and the semi-solid negative electrode. Also, for example, the above-mentioned relationship may be achieved only by the positive electrode active material of the semi-solid positive electrode. Also, for example, the above-mentioned relationship may be achieved only by the negative electrode active material of the semi-solid negative electrode. In a preferred embodiment of the present invention, the above-mentioned relationship is achieved by at least the positive electrode active material of the semi-solid positive electrode.

[0021] When the above relational expression is satisfied by the positive electrode active material of the semi-solid positive electrode, the above "particle size D10 (μm) of the active material" and "r of the active material" correspond to "particle size D10 (μm) of the positive electrode active material" and "r of the positive electrode active material", respectively. When the above relational expression is satisfied by the negative electrode active material of the semi-solid negative electrode, the above "particle size D10 (μm) of the active material" and "r of the active material" correspond to "particle size D10 (μm) of the negative electrode active material" and "r of the negative electrode active material", respectively.

[0022] The particle size D10 (μm) of an active material is the particle size at which the cumulative particle volume from the small particle size side reaches 10% of the total particle volume in the particle size distribution obtained by the laser diffraction / scattering method. Therefore, D10 (μm) refers to the above-mentioned specified particle size when the cumulative frequency of the active material from the minimum particle size to the specified particle size is 10%.

[0023] The particle size D10 (μm) of the active material can be measured by determining the particle size distribution by the laser diffraction / scattering method using a semi-solid electrode layer taken out of a secondary battery as a sample. The particle size distribution measuring device is not particularly limited as long as it is a measuring device using the laser diffraction / scattering method, and for example, a commercially available LA-960 (manufactured by Horiba, Ltd.) can be used. The measured particle size distribution usually shows the particle size distribution of each material such as the conductive assistant and the electrode active material overlapping, but the particle size D10 (μm) of the active material can be measured by decomposing the particle size distribution of each material and identifying the materials that make up each particle size distribution. In addition, if the particle size distribution overlaps greatly and it is difficult to resolve the particle size distribution, the electrode can be diluted with an organic solvent such as NMP, and the particle size distribution can be measured after separating each material using the specific gravity difference of the particles.

[0024] The particle size D10 (μm) of the active material can be controlled by adjusting the particle size D10 (μm) of the active material used. For example, the particle size D10 (μm) of the active material can be made larger by using an active material with a larger D10 (μm). Also, for example, the particle size D10 (μm) of the active material can be made smaller by using an active material with a smaller D10 (μm). The particle size D10 (μm) of the active material can be controlled by classification. For example, the particle size D10 (μm) of the active material can be made larger by removing small diameter particles from the active material by classification. Also, for example, the particle size D10 (μm) of the active material can be made smaller by removing large diameter particles from the active material by classification.

[0025] The particle size D90 (μm) of an active material is the particle size at which the cumulative particle volume from the small particle size side reaches 90% of the total particle volume in the particle size distribution obtained by a laser diffraction / scattering method. Therefore, D90 (μm) refers to the above-mentioned specified particle size when the cumulative frequency obtained by accumulating the frequencies from the minimum particle size of the active material to the specified particle size is 90%.

[0026] The r of an active material corresponds to the diameter r of a sphere inscribed in a tetrahedral gap formed by four closely packed spheres with a diameter of D90, as shown in Figure 1. In other words, the r of an active material means the maximum diameter of a sphere that can enter the gap surrounded by four closely packed active material particles of D90 when the active material particles of D90 form a closely packed structure.

[0027] The particle size D90 (μm) of the active material can be measured by determining the particle size distribution by the laser diffraction / scattering method using a semi-solid electrode layer taken out of a secondary battery as a sample. The particle size distribution measuring device is not particularly limited as long as it is a measuring device using the laser diffraction / scattering method, and for example, a commercially available LA-960 (manufactured by Horiba, Ltd.) can be used. The measured particle size distribution usually shows the particle size distribution of each material such as the conductive assistant and the electrode active material overlapping, but the particle size D90 (μm) of the active material can be measured by decomposing the particle size distribution of each material and identifying the materials that make up each particle size distribution. In addition, if the particle size distribution overlaps greatly and it is difficult to decompose the particle size distribution, the electrode can be diluted with an organic solvent such as NMP, and the particle size distribution can be measured after separating each material by utilizing the specific gravity difference of the particles. The particle size D90 (μm) of the active material obtained can be substituted into the above formula (1) to calculate the r of the active material.

[0028] The particle size D90 (μm) of the active material can be controlled by adjusting the particle size D90 of the active material used. For example, by using an active material with a larger D90, the particle size D90 (μm) of the active material can be made larger. Also, for example, by using an active material with a smaller D90, the particle size D90 (μm) of the active material can be made smaller. The particle size D90 of the active material can be controlled by classification. For example, by removing small diameter particles from the active material by classification, the particle size D90 (μm) of the active material can be made larger. Also, for example, by removing large diameter particles from the active material by classification, the particle size D90 (μm) of the active material can be made smaller.

[0029] The particle size D10 (μm) of the active material is not particularly limited as long as the above relational formula is satisfied, and may be, for example, 2.0 μm or more and 20.0 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, the particle size D10 (μm) is preferably 3.0 μm or more and 18.0 μm or less, more preferably 4.0 μm or more and 16.0 μm or less, even more preferably 6.0 μm or more and 16.0 μm or less, particularly preferably 8.0 μm or more and 14.0 μm or less, and especially preferably 10.0 μm or more and 14.0 μm or less.

[0030] The particle size D90 (μm) of the active material is not particularly limited as long as the above relational formula is satisfied, and may be, for example, 10.0 μm or more and 70.0 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, the particle size D90 (μm) is preferably 15.0 μm or more and 60.0 μm or less, more preferably 20.0 μm or more and 55.0 μm or less, even more preferably 25.0 μm or more and 50.0 μm or less, particularly preferably 30.0 μm or more and 45.0 μm or less, and especially preferably 35.0 μm or more and 40.0 μm or less.

[0031] The r of the active material is not particularly limited as long as the above relational formula is satisfied, and may be, for example, 2.2 μm or more and 15.7 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, the r is preferably 3.4 μm or more and 13.5 μm or less, more preferably 4.5 μm or more and 12.4 μm or less, even more preferably 5.6 μm or more and 11.2 μm or less, particularly preferably 6.7 μm or more and 10.1 μm or less, and especially preferably 7.9 μm or more and 9.0 μm or less.

[0032] It is desirable that the particle size D10 (μm) of the active material and r of the active material satisfy the following relationship from the viewpoints of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics: Preferably, 0 <D10(μm)-r(μm)≦9; More preferably, 0.5 <D10(μm)-r(μm)≦7; More preferably, 0.5 <D10(μm)-r(μm)≦5; Particularly preferably, 1.0 <D10(μm)-r(μm)≦5; Especially preferred is 2.0 <D10(μm)-r(μm)≦5。

[0033] In the secondary battery of the present invention, by satisfying the above-mentioned relational expression, the active material particles are more sufficiently suppressed from changing over time in the internal structure of the electrode, for example, by settling, and therefore the rate characteristics and cycle characteristics of the secondary battery can be more sufficiently prevented from deteriorating. In detail, as shown in FIG. 2, when the active material particles having a particle size D10 (μm) are larger than the r (μm) of the active material, the active material particles having a particle size D10 cannot pass through the gaps surrounded by the close-packed active material particles of D90. Therefore, the active material particles having a particle size D10 do not settle, and the internal structure of the electrode is suppressed from changing over time. On the other hand, as shown in FIG. 3, when the particle size D10 (μm) of the active material particles is equal to or less than the r (μm) of the active material, the active material particles having a particle size D10 pass through the gaps surrounded by the close-packed active material particles of D90. Therefore, the active material particles settle, and the internal structure of the electrode changes over time, resulting in a decrease in the rate characteristics and cycle characteristics.

[0034] The positive electrode active material contained in the positive electrode and the negative electrode active material contained in the negative electrode of the secondary battery of the present invention are materials directly involved in the transfer of electrons in the secondary battery, and are the main materials of the positive and negative electrodes that are responsible for charging and discharging, i.e., the battery reaction. More specifically, ions are brought to the electrolyte due to the "positive electrode active material contained in the positive electrode" and the "negative electrode active material contained in the negative electrode", and these ions move between the positive electrode and the negative electrode to transfer electrons and charge and discharge. Such mediator ions are not particularly limited as long as they can be charged and discharged, and examples thereof include lithium ions or sodium ions (particularly lithium ions). The positive electrode and the negative electrode may be electrodes that can particularly absorb and release lithium ions. In other words, the secondary battery of the present invention may be a secondary battery in which lithium ions move between the positive electrode active material and the negative electrode active material via the electrolyte to charge and discharge the battery. When lithium ions are involved in charging and discharging, the secondary battery of the present invention corresponds to a so-called "lithium ion battery".

[0035] The positive electrode active material of the positive electrode is preferably made of, for example, granular material. Furthermore, it is also preferable that a conductive assistant is contained in the positive electrode (particularly the positive electrode layer) in order to facilitate the transfer of electrons that promote the battery reaction. Similarly, the negative electrode active material of the negative electrode is preferably made of, for example, granular material, and a conductive assistant may be contained in the negative electrode (particularly the negative electrode layer) in order to facilitate the transfer of electrons that promote the battery reaction. In this way, since a plurality of components are contained, the positive electrode layer and the negative electrode layer can also be called "positive electrode composite layer" and "negative electrode composite layer", respectively.

[0036] The positive electrode active material is preferably a material that contributes to the absorption and release of lithium ions. From this viewpoint, the positive electrode active material is preferably, for example, a lithium-containing composite oxide. More specifically, the positive electrode active material is preferably a lithium transition metal composite oxide containing lithium and at least one transition metal selected from the group consisting of cobalt, nickel, manganese, and iron. That is, in the positive electrode layer of the secondary battery according to the present invention, such a lithium transition metal composite oxide is preferably contained as the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium iron phosphate, or a material in which a part of the transition metal is replaced with another metal. Such a positive electrode active material may be contained as a single type, or may be contained in a combination of two or more types. In a more preferred embodiment, the positive electrode active material contained in the positive electrode (particularly the positive electrode layer) is lithium cobalt oxide.

[0037] The average particle size of the positive electrode active material is not particularly limited and may be, for example, 1 μm or more and 100 μm or less, particularly 1 μm or more and 50 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, the average particle size is preferably 1 μm or more and 30 μm or less, more preferably 10 μm or more and 30 μm or less, even more preferably 15 μm or more and 30 μm or less, and particularly preferably 22 μm or more and 30 μm or less.

[0038] The average particle size of the positive electrode active material is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.

[0039] The content of the positive electrode active material is usually 50% by mass or more and 90% by mass or less with respect to the total amount of the positive electrode layer, and from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, it is preferably 70% by mass or more and 90% by mass or less. The total amount of the positive electrode layer means the total content of each component (e.g., positive electrode active material, conductive assistant, electrolyte) constituting the positive electrode layer excluding the current collector.

[0040] The conductive assistant that may be contained in the positive electrode is not particularly limited, but may be at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black, carbon fibers such as graphite, carbon nanotubes, and vapor-grown carbon fibers, metal powders such as copper, nickel, aluminum, and silver, and polyphenylene derivatives. In a more preferred embodiment, the conductive assistant of the positive electrode layer is carbon black. In a further preferred embodiment, the positive electrode active material and conductive assistant of the positive electrode layer are a combination of lithium cobalt oxide and carbon black.

[0041] The average particle size of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is not particularly limited and may be, for example, 0.1 μm or more and 20 μm or less, particularly 0.1 μm or more and 10 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, it is preferably 0.5 μm or more and 8 μm or less, more preferably 1 μm or more and 5 μm or less.

[0042] The average particle size of the conductive additive contained in the positive electrode (particularly the positive electrode layer) is the particle size D50 at which the accumulated particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.

[0043] The content of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is usually 0.1 mass % or more and 10 mass % or less, relative to the total amount of the positive electrode layer, and from the viewpoints of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, the content is preferably 0.5 mass % or more and 5 mass % or less, more preferably 0.5 mass % or more and 3.5 mass % or less, and particularly preferably 0.5 mass % or more and 2 mass % or less.

[0044] The negative electrode active material is preferably a material that contributes to the absorption and release of lithium ions. From this point of view, the negative electrode active material is preferably, for example, various carbon materials, oxides, or lithium alloys. Examples of various carbon materials for the negative electrode active material include graphite (natural graphite, artificial graphite), hard carbon, soft carbon, and diamond-like carbon. In particular, graphite is preferable because of its high electronic conductivity. Examples of oxides for the negative electrode active material include at least one selected from the group consisting of silicon oxide, tin oxide, indium oxide, zinc oxide, and lithium oxide. The lithium alloy for the negative electrode active material may be any metal that can form an alloy with lithium, and may be, for example, a binary, ternary, or more alloy of lithium and a metal such as Al, Si, Pb, Sn, In, Bi, Ag, Ba, Ca, Hg, Pd, Pt, Te, Zn, or La. It is preferable that such oxides have an amorphous structure. This is because deterioration caused by non-uniformity such as grain boundaries or defects is less likely to occur. In a more preferred embodiment, the negative electrode active material of the negative electrode is artificial graphite.

[0045] The average particle size of the negative electrode active material is not particularly limited and may be, for example, 0.5 μm or more and 50 μm or less, particularly 1 μm or more and 40 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, it is preferably 2 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less.

[0046] The average particle size of the negative electrode active material is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.

[0047] The content of the negative electrode active material is usually 10% by mass or more and 50% by mass or less with respect to the total amount of the negative electrode layer, and from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, it is preferably 15% by mass or more and 35% by mass or less. The total amount of the negative electrode layer means the total content of each component (e.g., negative electrode active material, conductive assistant, electrolyte) constituting the negative electrode layer excluding the current collector.

[0048] The conductive assistant that may be contained in the negative electrode is not particularly limited, but may include at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black; carbon fibers such as carbon nanotubes and vapor-grown carbon fibers; metal powders such as copper, nickel, aluminum, and silver; and polyphenylene derivatives.

[0049] The average particle size of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is not particularly limited and may be, for example, 0.1 μm or more and 20 μm or less, particularly 0.1 μm or more and 10 μm or less. From the viewpoint of suppressing changes over time in the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, it is preferably 0.5 μm or more and 8 μm or less, more preferably 1 μm or more and 5 μm or less.

[0050] The average particle size of the conductive additive contained in the negative electrode (particularly the negative electrode layer) is the particle size D50 at which the accumulated particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.

[0051] The content of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is usually 0% by mass or more and 10% by mass or less with respect to the total amount of the negative electrode layer, and from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics, it is preferably 0% by mass or more and 2% by mass or less, and more preferably 0% by mass. The content of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) being 0% by mass means that the negative electrode (particularly the negative electrode layer) does not contain the conductive assistant.

[0052] The electrolyte contained in the positive electrode and the electrolyte contained in the negative electrode usually have the same composition.

[0053] The electrolyte aids the movement of metal ions released from the electrode active materials (positive and negative active materials). The electrolyte may be a "non-aqueous" electrolyte such as an organic electrolyte or an organic solvent, or an "aqueous" electrolyte containing water. The secondary battery of the present invention is preferably a non-aqueous electrolyte secondary battery using an electrolyte containing a "non-aqueous" solvent and a solute as the electrolyte. The electrolyte may be in the form of a liquid or gel (note that in this specification, a "liquid" non-aqueous electrolyte is also referred to as a "nonaqueous electrolyte").

[0054] A specific solvent for the non-aqueous electrolyte is not particularly limited, and preferably contains at least a carbonate. Such carbonate may be a cyclic carbonate and / or a chain carbonate. Although not particularly limited, the cyclic carbonate may be at least one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC) and vinylene carbonate (VC). The chain carbonate may be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dipropyl carbonate (DPC). In one preferred embodiment, a combination of a cyclic carbonate and a chain carbonate is used as the non-aqueous electrolyte, for example, a mixture of ethylene carbonate and ethyl methyl carbonate is used.

[0055] As a specific solute of the non-aqueous electrolyte, for example, Li salts such as LiPF6 and LiBF4 are preferably used. In a preferred embodiment, LiPF6 is used. The concentration of the solute in the electrolyte is not particularly limited, and may be, for example, 0.1M or more and 10M or less, particularly 0.5M or more and 3M or less. M is mol / L.

[0056] The content of the electrolyte in the positive electrode (particularly the positive electrode layer) and the negative electrode (particularly the negative electrode layer) is not particularly limited. For example, the content of the electrolyte in the positive electrode (particularly the positive electrode layer) is usually 5% by mass or more and 40% by mass or less, and particularly 5% by mass or more and 35% by mass or less, based on the total amount of the positive electrode layer. For example, the content of the electrolyte in the negative electrode (particularly the negative electrode layer) is usually 10% by mass or more and 30% by mass or less, and particularly 15% by mass or more and 25% by mass or less, based on the total amount of the negative electrode layer.

[0057] The thickness of the electrode layer is not particularly limited and may be appropriately selected according to the desired battery capacity. The thickness of the electrode layer (particularly the thickness of the electrode layer per one main surface (one side) of the current collector described later) is, for example, such a thickness that the capacity per electrode area on one side in the secondary battery of the present invention falls within the range described later, and is usually 80 μm or more, particularly 150 μm or more and 500 μm or less. The thickness of the electrode layer includes the thickness of the positive electrode layer and the thickness of the negative electrode layer, and each may be selected independently. The thickness of the electrode layer is the average value of the thicknesses at any 50 points in the completed secondary battery.

[0058] The electrode (particularly the semi-solid electrode) 1 is usually provided with an electrode layer (particularly the semi-solid electrode layer) on at least one side (preferably both sides) of a current collector. The constituent material of the current collector is not particularly limited as long as it has electrical conductivity, and may be, for example, one metal selected from the group consisting of copper, aluminum, stainless steel, etc., or an alloy containing two or more metals. The current collector of the positive electrode is preferably made of aluminum from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics. The current collector of the negative electrode is preferably made of copper from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics.

[0059] There are no particular limitations on the thickness of the positive electrode and negative electrode current collectors, and they may each independently be, for example, from 1 μm to 300 μm, particularly from 1 μm to 100 μm.

[0060] The secondary battery of the present invention is usually enclosed in an exterior body. The exterior body may be a flexible pouch (soft bag) or a hard case (hard housing). From the viewpoint of suppressing the change over time of the electrode internal structure and further improving the rate characteristics and cycle characteristics, the exterior body is preferably a flexible pouch.

[0061] When the exterior body is a flexible pouch, the flexible pouch is usually formed from a laminate film, and the seal part is formed by heat-sealing the periphery. The laminate film is generally a film in which a metal foil and a polymer film are laminated, and specifically, a three-layer structure consisting of an outer layer polymer film / metal foil / inner layer polymer film is exemplified. The outer layer polymer film is for preventing damage to the metal foil due to permeation of moisture and the like and contact, and polymers such as polyamide and polyester can be suitably used. The metal foil is for preventing permeation of moisture and gas, and foils such as copper, aluminum, and stainless steel can be suitably used. The inner layer polymer film is for protecting the metal foil from the electrolyte stored inside and for melt sealing during heat sealing, and polyolefin or acid-modified polyolefin can be suitably used. The thickness of the laminate film is not particularly limited, and is preferably 1 μm or more and 1 mm or less. For example, in the case of a secondary battery having a rectangular shape in plan view, the exterior body is usually heat-sealed at its periphery in plan view. Specifically, when the exterior body is made of two rectangular exterior body materials, the exterior body is usually heat-sealed at its four sides in plan view, and when the exterior body is made of one rectangular exterior body material, one of the four sides in plan view is usually formed by folding back the exterior body material.

[0062] When the exterior body is a hard case, the hard case is usually formed from a metal plate, and the sealing portion is formed by irradiating the peripheral portion with a laser. The metal plate is generally made of a metal material such as aluminum, nickel, iron, copper, or stainless steel. The thickness of the metal plate is not particularly limited, and is preferably, for example, 1 μm or more and 1 mm or less. The sealing of the metal plates may be achieved by irradiating the overlapping portion of the peripheral portion with a laser.

[0063] The secondary battery 10 of the present invention is effective in increasing the capacity. Since the electrode layer is a semi-solid electrode layer and has fluidity, the thickness of the electrode layer can be stably and easily increased simply by increasing the amount of the electrode layer injected. From this viewpoint, the capacity per electrode area on one side of the secondary battery of the present invention is preferably 4 mAh / cm. 2 More preferably, 5 mAh / cm 2 More than 20mAh / cm 2 The capacitance per electrode area may be the capacitance per current collector area since the electrode layer in the present invention is a semi-solid electrode layer. The capacitance per electrode area of ​​the positive electrode and the negative electrode may be independently within the above range. When the electrode layer is provided on both sides of the current collector, the capacitance per electrode area is the capacitance per one side.

[0064] The capacity per electrode area in the secondary battery of the present invention may be the active material capacity per electrode area. The capacity per electrode area may be controlled, for example, by adjusting the amount of slurry containing the active material injected into the electrode. Specifically, the capacity per electrode area may be controlled by adjusting the amount of slurry containing the active material injected into the electrode so as to obtain a predetermined active material capacity per electrode area. The capacity per electrode area includes both the positive electrode and the negative electrode, and the capacity per area of ​​the positive electrode and the negative electrode can be controlled by the same method as the above control method.

[0065] [Secondary battery manufacturing method] The secondary battery of the present invention can be produced by a method including the following steps: a particle size adjusting step of adjusting the particle size of the electrode active material; a preparation step of mixing the particle size-adjusted electrode active material and the electrolyte to prepare a slurry for electrode layers (i.e., a slurry for a positive electrode layer and a slurry for a negative electrode layer); A coating process of coating a current collector with a slurry for electrode layers to form electrodes (i.e., positive and negative electrodes); A lamination step of laminating the electrodes to form a laminate such that a separator is disposed between the electrodes (i.e., between the positive electrode and the negative electrode); and An encapsulation step of encapsulating the laminate in an exterior case.

[0066] The method for producing a secondary battery of the present invention may usually include the following steps immediately after the coating step: A welding process in which a tab is welded to an electrode.

[0067] The method for producing a secondary battery of the present invention may further include, after the encapsulating step, the following steps in sequence: A charge-discharge process in which a solid electrolyte interfacial coating is formed on the surface of the negative electrode active material by an initial charging process to form a secondary battery precursor; and An aging step of aging the secondary battery precursor.

[0068] In the particle size adjustment step, specifically, the positive electrode active material is classified by a sieve shaker, and the negative electrode active material is classified by a sieve shaker.

[0069] In the preparation step, specifically, a positive electrode layer slurry is prepared by mixing and dispersing a particle size-adjusted positive electrode active material, an electrolyte, and a desired additive and a desired conductive assistant, and a negative electrode layer slurry is prepared by mixing and dispersing a negative electrode active material, an electrolyte, and a desired conductive assistant.

[0070] In the coating step, specifically, the positive electrode layer slurry is coated on a positive electrode current collector to form a positive electrode, and the negative electrode layer slurry is coated on a negative electrode current collector to form a negative electrode. In forming the positive electrode and the negative electrode, the electrode layer slurry is coated independently on at least one surface (preferably both surfaces) of the current collector.

[0071] Then, a welding step may be performed. In the welding step, specifically, a positive electrode tab is welded to the positive electrode. Also, a negative electrode tab is welded to the negative electrode. The material constituting the positive electrode tab and the negative electrode tab is not particularly limited as long as it has electrical conductivity, and may be selected from, for example, the same material as the constituting material of the current collector. The positive electrode tab is preferably made of aluminum from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics. The negative electrode tab is preferably made of copper from the viewpoint of suppressing the change over time of the internal structure of the electrode and further improving the rate characteristics and cycle characteristics. The welding step may be performed before (particularly immediately before) the coating step.

[0072] In the lamination step, specifically, positive and negative electrodes are laminated so that the positive and negative electrodes are alternately arranged with a separator disposed therebetween to produce a laminate. The laminate is then sandwiched between exterior body materials. The sandwiching is not particularly limited as long as exterior bodies are arranged at the top and bottom of the laminate in a plan view, and may be achieved, for example, by the following method (i) or (ii): Method (i) sandwiching the laminate between two sheets of exterior material; Method (ii) The laminate is housed in a bag-shaped exterior body having an opening on one side in a plan view, the bag-shaped exterior body having been formed in advance by sealing. In the method (i), instead of the two sheets of exterior body material, one continuous sheet of exterior body material may be folded back.

[0073] In the encapsulation step, more specifically, the overlapping portion at the periphery of the exterior body material is sealed, and the inside of the exterior body is evacuated. In the sandwiching step, when method (i) is employed, the inside of the exterior body is evacuated while the periphery of the exterior body material is sealed at the overlapping portion. When method (ii) is employed, the inside of the exterior body is evacuated while the opening of the bag-shaped exterior body is sealed at the overlapping portion. The overlapping portion refers to the overlapping portion between the exterior body materials.

[0074] Subsequently, a charge / discharge step and an aging step may be performed. In the charge / discharge process, specifically, a solid electrolyte interface coating (hereinafter referred to as "SEI coating") is formed on the surface of the negative electrode active material by an initial charging treatment.

[0075] The initial charging process is a first charging process performed for the purpose of forming an SEI film on the surface of the negative electrode active material, and is also called a conditioning process or a formation process. The SEI film is formed by the reductive decomposition of an additive contained in the electrolyte on the surface of the negative electrode active material in this process, and prevents further decomposition of the additive on the surface of the negative electrode active material during use as a secondary battery. The SEI film usually contains one or more substances selected from the group consisting of LiF, Li2CO3, LiOH, and LiOCOOR (R represents a monovalent organic group, for example, an alkyl group). By forming such an SEI film more uniformly on the surface of the negative electrode active material, decomposition of the electrolyte components in the secondary battery can be prevented, and the capacity stabilization and long life of the secondary battery can be achieved.

[0076] In the initial charging process, charging may be performed at least once. Usually, charging and discharging are performed one or more times. One charging and discharging includes one charging and one subsequent discharging. When charging and discharging are performed two or more times, the charging and discharging are repeated the corresponding number of times. The number of charging and discharging performed in this process is usually from one to three.

[0077] The charging method may be a constant current charging method or a constant voltage charging method, or a combination of these. For example, constant voltage charging and constant voltage charging may be repeated during one charging. The charging conditions are not particularly limited as long as the SEI coating is formed. From the viewpoint of further improving the uniformity of the thickness of the SEI coating, it is preferable to perform constant current charging and then constant voltage charging.

[0078] The discharge method may be a constant current discharge method or a constant voltage discharge method, or a combination of these. The discharge conditions are not particularly limited as long as the SEI film is formed. From the viewpoint of further improving the uniformity of the thickness of the SEI film, it is preferable to perform constant current discharge.

[0079] In the initial charging process, the secondary battery is usually maintained at a temperature within the range of 25°C to 100°C, preferably within the range of 35°C to 90°C, and more preferably within the range of 40°C to 85°C.

[0080] In the aging process, more specifically, the SEI film is stabilized by a stabilization treatment, which is a treatment for stabilizing the SEI film by leaving the secondary battery after the initial charging treatment in an open circuit state.

[0081] The temperature of the secondary battery in the stabilization treatment is not particularly limited, and may be maintained within a range of, for example, 15° C. or more and 80° C. or less. From the viewpoint of further stabilizing the SEI coating, the secondary battery is preferably maintained at a temperature within a range of 20° C. or more and 75° C. or less, and more preferably at a temperature within a range of 25° C. or more and 70° C. or less. In detail, the temperature can be maintained within the above range by leaving the secondary battery in a space set at a constant temperature.

[0082] The time for which the material is left in the stabilization treatment is not particularly limited as long as the stabilization of the SEI coating is promoted, and is usually from 10 minutes to 30 days. From the viewpoint of further stabilizing the SEI coating, the time is preferably within the range of from 30 minutes to 14 days, and more preferably within the range of from 1 hour to 7 days.

[0083] The manufacturing method of the secondary battery according to the present invention only includes a particle size adjustment step, a mixing step, and a coating step as electrode manufacturing steps, and only includes a welding step, a lamination step, an encapsulation step, a charge / discharge step, and an aging step as assembly steps.

[0084] On the other hand, a conventional method for producing a secondary battery including a binder-bonded electrode layer includes, as electrode production steps, a preparation step of preparing an electrode layer-forming coating liquid; a coating step of coating a current collector with the electrode layer-forming coating liquid; a drying step of drying the applied electrode layer-forming coating liquid; a pressing step of compacting the electrode layer; a slitting step of cutting the electrode to a desired width; and a cutting step of cutting the electrode cut to the desired width into a desired shape and size to obtain an electrode, and includes, as assembly steps, a welding step of welding a tab to the electrode; a lamination step of laminating the electrodes so that the positive and negative electrodes constituting the electrodes are arranged alternately with a separator arranged between them to produce a laminate; a liquid injection step of sandwiching the produced laminate within an outer casing and injecting an electrolyte into the outer casing; an impregnation step of impregnating the electrodes with the electrolyte under vacuum; and an enclosure step of enclosing the laminate in the outer casing; a charge / discharge step of forming a solid electrolyte interface film on the surface of the negative electrode active material by an initial charging treatment to form a secondary battery precursor; and an aging step of aging the secondary battery precursor. Therefore, in the method for producing a secondary battery according to the present invention, both the electrode production process and the assembly process are greatly simplified, making it possible to achieve a dramatic reduction in capital investment and manufacturing process costs. EXAMPLES

[0085] <Secondary battery manufacturing> Particle size adjustment (classification) The positive electrode active material (lithium cobalt oxide (LCO)) was classified using a sieve shaker to obtain a positive electrode active material having a particle size distribution of D10 = 12.0 μm, D90 = 36.0 μm, and D50 (average particle size) = 23.1 μm, a positive electrode active material having a particle size distribution of D10 = 4.2 μm, D90 = 15.6 μm, and D50 (average particle size) = 10.5 μm, a positive electrode active material having a particle size distribution of D10 = 4.0 μm, D90 = 32.0 μm, and D50 (average particle size) = 16.3 μm, and a positive electrode active material having a particle size distribution of D10 = 7.5 μm, D90 = 34.2 μm, and D50 (average particle size) = 21.0 μm.

[0086] (Example 1: Semi-solid electrode type secondary battery) Positive electrode preparation Lithium cobalt oxide (LCO) with particle sizes D10 = 12.0 μm and D90 = 36.0 μm was used as the positive electrode active material, carbon black with an average particle size of 2.8 μm was used as the conductive additive, and a solution of 1M LiPF6 was dissolved in a mixed solvent (EC:EMC = 25:75 vol) as the electrolyte was mixed and dispersed in a weight ratio of 81:1:18 to obtain a positive electrode layer slurry with good fluidity. The positive electrode layer slurry was applied to a positive electrode active material capacity of one side of 5.0 mAh / cm 2 The solution was applied to an Al foil having a thickness of 15 μm by a doctor blade method to an area of ​​10.0 cm×10.0 cm to obtain a positive electrode.

[0087] Negative electrode preparation The negative electrode active material was artificial graphite with an average particle size of 10.2 μm, and the electrolyte was a solution of 1M LiPF6 dissolved in a mixed solvent (EC:EMC = 25:75 vol). These were mixed and dispersed in a weight ratio of 60.0:40.0 to obtain a fluid negative electrode layer slurry. The negative electrode layer slurry was applied to the negative electrode active material on one side so that the capacity of the negative electrode active material on one side was 5.4 mAh / cm. 2 The solution was applied to one side of a 12 μm thick Cu foil by a doctor blade method to obtain a negative electrode having an area of ​​10.2 cm×10.2 cm.

[0088] Secondary battery production The tab-welded positive and negative electrodes were attached to each other with a separator between them, sandwiched between aluminum laminates, and vacuum sealed. After charging and discharging at 0.2 CA, the battery was charged to SOC 70% and aged at 55°C for 24 hours to complete a cell with a capacity of approximately 500 mAh. In the semi-solid positive electrode, the binder content was 0.01 mass% or less with respect to the total amount of the semi-solid positive electrode layer in the secondary battery completed in this example. In the semi-solid negative electrode, the binder content was 0.01 mass% or less with respect to the total amount of the semi-solid negative electrode layer in the secondary battery completed in this example. The thickness of the separator was 20 μm.

[0089] (Example 2: Semi-solid electrode type secondary battery) A secondary battery was obtained in the same manner as in Example 1, except that lithium cobalt oxide (LCO) having particle sizes D10=4.2 μm and D90=15.6 μm was used as the positive electrode active material in producing the positive electrode.

[0090] (Comparative Example 1: Binder-bonded electrode type secondary battery) Positive electrode preparation Lithium cobalt oxide (LCO) with an average particle size of 15 μm (particle size D10 = 4.0 μm and D90 = 32.0 μm) was used as the positive electrode active material, carbon black with an average particle size of 1 μm was used as the conductive additive, and PVdF was used as the binder, and dispersed in NMP in a weight ratio of 96:2:2 to obtain a positive electrode slurry. Next, a die coater was used to coat the active material on one side so that the capacity of the active material was 5.0 mAh / cm. 2 After applying the mixture to one side of an Al foil with a thickness of 15 μm and drying it, the mixture was compressed using a roll press machine so that the porosity was 20%, and then slit and cut to obtain a positive electrode of 10.0 cm × 10.0 cm.

[0091] Negative electrode preparation The negative electrode slurry was obtained by dispersing artificial graphite with an average particle size of 10 μm as the negative electrode active material, flake graphite with an average particle size of 3 μm as the conductive assistant, and CMC and SBR as the binder in a weight ratio of 96:1:3 (1.5 + 1.5) in water. Then, the active material capacity on one side was 5.4 mAh / cm using a die coater. 2 After coating and drying on one side of a 12 μm thick Cu foil so that the porosity was 23%, the foil was compressed using a roll press machine, and then slit and cut to obtain a negative electrode of 10.2 cm × 10.2 cm.

[0092] Secondary battery production The tab-welded positive and negative electrodes were laminated together with a separator between them, sandwiched between aluminum laminates, and a 1M electrolyte solution of LiPF6 dissolved in a mixed solvent (EC:EMC=25:75vol) was poured into the battery, which was then vacuum-impregnated and vacuum-sealed. After charging and discharging at 0.2CA, the battery was charged to SOC70% and aged at 55℃ for 24 hours to complete a secondary battery with a capacity of approximately 500mAh.

[0093] (Comparative Example 2: Semi-Solid Electrode Type Secondary Battery) A secondary battery was obtained in the same manner as in Example 1, except that lithium cobaltate (LCO) with a particle size D10 = 4.0 μm and D90 = 32.0 μm was used as the positive electrode active material when fabricating the positive electrode.

[0094] (Comparative Example 3: Semi-Solid Electrode Type Secondary Battery) A secondary battery was obtained in the same manner as in Example 1, except that lithium cobaltate (LCO) with a particle size D10 = 7.5 μm and D90 = 34.2 μm was used as the positive electrode active material when fabricating the positive electrode.

[0095] (Evaluation and Measurement) (Particle Size D10 Value and D90 Value) The sample was dispersed in NMP while applying ultrasonic waves, and the particle size distribution was measured using a laser diffraction / scattering type particle size distribution measuring device (LA-960 manufactured by Horiba, Ltd.). The D10 value and D90 were obtained from the results.

[0096] (Initial Rate Characteristics and Rate Characteristics after 50 Days) The capacity retention rate X (0.2CA discharge capacity ratio) when each completed secondary battery was discharged at 2CA at 25°C was measured. The secondary battery was allowed to stand for 50 days, and the same measurement was performed again. The rate characteristics after 50 days were evaluated as follows. ◎; 85% < X (Best); 〇; 84% < X ≤ 85% (Good); △; 82% < X ≤ 84% (No Problem in Practical Use); ×; X ≤ 82% (Problem in Practical Use).

[0097] (Retention Rate of Rate Characteristics after 50 Days) The retention rate of the 2CA capacity retention rate (%) after 50 days with respect to the initial 2CA capacity retention rate (%) was calculated by the following calculation method. Retention Rate of Capacity Retention Rate after 50 Days (%) = (2CA Capacity Retention Rate X (%) after 50 Days / Initial 2CA Capacity Retention Rate X (%)) × 100 ◎; 98% < X (Best); 〇; 95% < X ≤ 98% (Good); △; 93% < X ≤ 95% (No problem in practical use); ×; X ≤ 93% (Problem in practical use).

[0098] (Cycle characteristics) Using each of the completed secondary batteries, the 0.2CA capacity retention rate Y was measured when full charge and discharge (3.00V to 4.35V) at a current of 0.5CA was repeated 300 cycles at 35°C. Specifically, the 0.2CA capacity retention rate Y is the ratio of the 0.2CA discharge capacity at the 300th cycle to the 0.2CA discharge capacity at the first cycle. ◎; 90% < Y (Best); ○; 89% < Y ≤ 90% (Good); △; 87% < Y ≤ 89% (No problem in practical use); ×; Y ≤ 87% (Problem in practical use).

[0099] Various evaluation levels and evaluation results are shown in Table 1.

[0100]

Table 1

[0101] The symbols in Table 1 are as follows. ※1: Blending, coating, drying, pressing, slitting, cutting ※2: Tab welding, laminate production, electrolyte injection, vacuum impregnation, encapsulation, charge and discharge, aging ※3: Particle size adjustment, blending, coating ※4: Tab welding, laminate production, encapsulation, charge and discharge, aging

[0102] In all examples and comparative examples, secondary batteries were fabricated in a very high areal density region of 5.0 mAh / cm 2 . Therefore, in Comparative Example 1 fabricated by a conventional method including a binder, the resistance is high, resulting in poor rate characteristics and cycle characteristics.

[0103] In Comparative Examples 2 and 3, which used fluid electrodes that did not contain a binder, the secondary battery manufacturing process was significantly simplified and the initial rate characteristics were improved. However, since the value of D10 was lower than the value of r, the rate characteristics and rate characteristic retention rate after standing for 50 days and the cycle characteristics after 300 cycles were relatively low.

[0104] On the other hand, in Examples 1 and 2 in which the value of D10 exceeded the value of r, the rate characteristics after being left standing for 50 days, the retention rate of the rate characteristics after being left standing for 50 days, and the cycle characteristics after 300 cycles showed high values, and the problem of deterioration over time was improved.

[0105] The secondary battery of the present invention can be used in various fields where battery use or storage is anticipated. By way of example only, the secondary battery of the present invention can be used in electronics packaging fields. The secondary battery according to an embodiment of the present invention can also be used in the electrical, information, and communication fields in which mobile devices and the like are used (e.g., electrical and electronic devices fields including small electronic devices such as mobile phones, smartphones, smart watches, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches, or mobile device fields), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household installation-type power storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like).

Claims

1. A semi-solid electrode having an electrode active material and an electrolyte, The particle size distribution of the electrode active material has the following relationship: D10 (μm)>r (μm) (In the formula, r is the diameter of a sphere inscribed in a tetrahedral gap formed by four spheres of close packing D90 (μm), and is expressed by the following formula: [0010] (represented by Secondary batteries meet these requirements.

2. the semi-solid electrode comprises a semi-solid positive electrode and a semi-solid negative electrode; The secondary battery according to claim 1 , wherein a particle size distribution of at least one of a positive electrode active material contained in the semi-solid positive electrode and a negative electrode active material contained in the semi-solid negative electrode satisfies the relational expression.

3. The secondary battery according to claim 1 , wherein the D10 (μm) is 2.0 μm or more and 20.0 μm or less.

4. The secondary battery according to any one of claims 1 to 3, wherein the D90 (μm) is 10.0 μm or more and 70.0 μm or less.

5. The secondary battery according to any one of claims 1 to 4, wherein the D10 (μm) and the r (μm) of the electrode active material satisfy the following relationship: 0<D10(μm)−r(μm)≦9.

6. The capacity per area of ​​the semi-solid electrode is 4 mAh / cm 2 The secondary battery according to any one of claims 1 to 5.

7. 7. The secondary battery according to claim 1, wherein the semi-solid electrode has an electrode layer capable of absorbing and releasing lithium ions.

8. A method for producing the secondary battery according to any one of claims 1 to 7, comprising the following steps: a particle size adjusting step of adjusting the particle size of the electrode active material; a preparation step of mixing the particle size-adjusted electrode active material and an electrolyte solution to prepare a slurry for an electrode layer; A coating step of coating a current collector with a slurry for an electrode layer to form an electrode; A lamination step of laminating the electrodes to form a laminate such that a separator is disposed between the electrodes; and an encapsulation step of encapsulating the laminate in an outer casing;

Citation Information

Patent Citations

  • Semi-solid electrodes with high speed capability

    JP2016500465A